CCTV Architectural Design for Theft Detection using Intruder Detection System - Kembuan, Eddy D.R.E; Batmetan, Johan Reimon; Daud, Metsi; Tarandung, Iszach R P (International Journal of Information Technology and Education, 2022)
The human need for a monitoring system for certain places is increasing. In this regard, the computer laboratory belonging to the school is not free from security intruders. Security bully or in English is usually called "intruder". Intruders can be thieves, vandals, or security intruders. In this paper, we will examine the design of the school computer laboratory CCTV architecture to examine the results of the implementation of an intruder detection system design that uses a CCTV architecture with SMK N 1 Tondano as its location and observes places and areas that are allowed. The results of this study are the formulation of the effect on performance in detecting intruders at SMK N 1 Tondano which we got through direct observation and interviews and with theoretical support from books, journals, internet and other sources.